Rural Poverty, Population Mobility, And Agrarian Change: A Historical Overview - Sihaloho, Martua; Sri Wahyuni, Ekawati; A. Kinseng, Rilus (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2016)
ABSTRACTTo overcome some economic difficulties, especially poverty, most poor people in the rural area decide to adopt a migration strategy (especially going to foreign countries). The decision to become international migrants contributes to the national economy (foreign exchange) at the macro level and their nuclear family (remittance) at the micro level. The remittance or cash money, in turn, enables them to meet their needs and even accumulate some assets (e.g. land and house) to be used as capital, resulting in a transformation of local agrarian structure. Some studies showed that the welfare of migrants’ families has increased significantly. Such an improved welfare of poor rural families has made rural community more dynamic in the vertical social mobility, including the efforts to extend their contract and motivate family members and the community to become international migrants (theory of cumulative causes, poverty-agrarian proposition, and poverty-migration proposition). This study has four initial hypotheses, namely: (1) change in agrarian structure affects poverty condition, (2) poverty (agrarian) affects population mobility, (3) population mobility (resulted remittance) affects agrarian structure, and (4) structural change in agraria causes new poverty. The diverse management and utilization of agrarian resources (poverty condition and the choice of population mobility —international migration) imply changes in the local agrarian structure which in turn produces new poverty and new agrarian classes.Keywords: agrarian structure, poverty, population mobility, persistenceABSTRAKMasyarakat miskin pedesaan pada akhirnya memilih menjadi pelaku migran dalam upaya mengatasi sejumlah kesulitan ekonomi (mengatasi masalah kemiskinan) yang dihadapinya. Pelaku migrasi mengambil keputusan dan berangkat menjadi migran pada akhirnya berkontribusi secara nasional (devisa negara) di aras makro dan terlebih di aras mikro (keluarga inti) pelaku migran-berupa remiten. Hasil remiten (khususnya ekonomi-uang) pada akhirnya dapat memenuhi kebutuhan keluarga dan bahkan mampu mengakumulasi asset (misal lahan dan rumah) untuk dijadikan modal bahkan ke arah perubahan struktur agraria lokal. Hasil dari beberapa penelitian menunjukkan peningkatan kesejahteraan keluarga pelaku migrasi. Perubahan kesejahteraan masyarakat miskin ini menjadi makin baik pada akhirnya mendinamisasi masyarakat pedesaan misalnya mobilitas sosial vertikal naik, termasuk upaya-upaya untuk melanjutkan kontrak menjadi pelaku migran, mendorong anggota keluarga dan komunitas menjadi pelaku migran (teori penyebab kumulatif, proposisi kemiskinan-agraria, proposisi kemiskinan-migrasi).Tiga hipotesis pengarah sebagai gagasan awal adalah (1) perubahan struktur agraria mempengaruhi kondisi kemiskinan; (2) kemiskinan (agraria) mempengaruhi laju gerak penduduk; (3) gerak penduduk (menghasilkan remiten) mempengaruhi perubahan struktur agraria, dan (3) perubahan struktur agraria menghasilkan kemiskinan baru. Ragam implikasi pengelolaan dan pemanfaatan sumberdaya agraria (kondisi kemiskinan dan pilihan gerak penduduk-migrasi internasional) berimplikasi pada perubahan struktur agraria dan selanjutnya menghasilkan kemiskinan baru dan golongan kelas baru.Kata Kunci: stuktur agraria, kemiskinan, gerak penduduk, persisten